Burnout and salutogenic functioning of nurses - F. Cilliers (AOSIS, 2003)
The aim of this research was to determine the nature of the relationship between burnout and salutogenic functioning, specifically sense of coherence, hardiness and learned resourcefulness. The measurement was done with the Maslach Burnout Inventory and the Antonovsky, Kobasa and Rosenbaum questionnaires, administered on a sample of 105 registered general nurses. Correlations, exploratory and confirmatory factor analysis are reported. The results indicate a significant negative correlation and a model of good fit, confirming a structural relationship between burnout and salutogenic functioning in its conceptualisation and its measurement. The nature of these relationships are discussed and recommendations are formulated towards more effective individual, group and organisational coping with and preventing of burnout.